2012
DOI: 10.1021/cm3011524
|View full text |Cite
|
Sign up to set email alerts
|

Mesostructured Block Copolymer Nanoparticles: Versatile Templates for Hybrid Inorganic/Organic Nanostructures

Abstract: We present a versatile strategy to prepare a range of nanostructured poly(styrene)-block-poly(2-vinyl pyridine) copolymer particles with tunable interior morphology and controlled size by a simple solvent exchange procedure. A key feature of this strategy is the use of functional block copolymers incorporating reactive pyridyl moieties which allow the absorption of metal salts and other inorganic precursors to be directed. Upon reduction of the metal salts, well-defined hybrid metal nanoparticle arrays could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
61
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 73 publications
1
61
0
Order By: Relevance
“…Polydisperse particles with different morphology and chemical heterogeneity can result in poor reproducibility and a variable property of the particles per batch. Some groups reported to fabricate uniform BCP particles using microfluidic method by which the particle diameters are ranged from hundreds nanometer to tens micrometer (Wang et al, 2010;Abate et al, 2011;Kuehne and Weitz, 2011), while other groups reported to prepare the structured BCP particles using membrane device (Tanaka et al, 2009;Connal et al, 2012;Deng et al, 2013), which enable a large-scale production of the particles but broader size distribution of the particles than that using microfluidic method. Therefore, it remains a challenge to produce large-scale and monodisperse structured BCP particles at sub-micrometer scale for practical application as mentioned above.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Polydisperse particles with different morphology and chemical heterogeneity can result in poor reproducibility and a variable property of the particles per batch. Some groups reported to fabricate uniform BCP particles using microfluidic method by which the particle diameters are ranged from hundreds nanometer to tens micrometer (Wang et al, 2010;Abate et al, 2011;Kuehne and Weitz, 2011), while other groups reported to prepare the structured BCP particles using membrane device (Tanaka et al, 2009;Connal et al, 2012;Deng et al, 2013), which enable a large-scale production of the particles but broader size distribution of the particles than that using microfluidic method. Therefore, it remains a challenge to produce large-scale and monodisperse structured BCP particles at sub-micrometer scale for practical application as mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the nitrogen atoms in PVP block have unpaired electrons which interact strongly with metal precursor (Hayward et al, 2005;Chai et al, 2007). For example, Connal et al (2012) have fabricated hybrid PS-b-P2VP particles by selectively infiltrating Au precursors (HAuCl 4 ) into the P2VP domain. In addition, they prepared mesoporous metal-oxide particles from PS-b-P2VP particles containing metal-oxide precursors after removing the BCP template by calcination.…”
Section: In Situ Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This self-assembly behavior is normally driven by a variety of covalent interaction and noncovalent interactions (e.g., electrostatics, hydrogen bonding, and van der Waals interactions). In terms of morphology versatility, copolymers with amphiphilic characteristic can self-assemble into various structures such as micelles, vesicles in their aqueous or organic solution, and lamellar, hexagonally packed cylinder, spherical, and gyroid structures in their solid bulk [6][7][8][9][10][11]. The size and morphology of these ordered structures are dependent on the composition, molecular weight, processing characteristics, especially on the balance between the hydrophobic domains and the hydrophilic domains.…”
mentioning
confidence: 99%
“…[ 1417 ] Recently it has been reported that bulk-type morphologies can be accessed in solution processing of BCPs. [ 1829 ] However, despite the potential of supramolecular chemistry to dictate the solution self-assembly of hydrophobic BCPs, systematic design rules to control nanostructures on demand are still limited. Importantly, these responsive assemblies would enable the development of new, complex, and multi-component soft nanostructures.…”
mentioning
confidence: 99%